2003
DOI: 10.1103/physrevb.67.134522
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific hole concentrations inBi2Sr2(Y

Abstract: Induction of holes not only in the superconductive CuO 2 plane but also in the Bi 2 O 2+δ charge reservoir of the Bi 2 Sr 2 (Y 1-x Ca x )Cu 2 O 8+δ superconductor upon Ca II -for-Y III substitution is evidenced by means of two independent techniques, i.e., high-resolution x-ray-absorption near-edge structure (XANES) spectroscopy measurements and coulometric redox titrations. The absolute values derived for the CuO 2 -plane hole concentration from the Cu L 2,3 -edge XANES spectra are in good agreement with thos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…From this procedure the error in the density of doped holes is estimated to be lower than 5%. Karppinen et al [13] have specified an error for this method of ± 0.02 holes. The results of the hole concentrations for the Pb-free and Pb-doped single-layer BISCO series are given in Fig 3 (a).…”
Section: Copper L 3 -Edge and Hole Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…From this procedure the error in the density of doped holes is estimated to be lower than 5%. Karppinen et al [13] have specified an error for this method of ± 0.02 holes. The results of the hole concentrations for the Pb-free and Pb-doped single-layer BISCO series are given in Fig 3 (a).…”
Section: Copper L 3 -Edge and Hole Concentrationmentioning
confidence: 99%
“…For the determination of the intensity of the prepeak, an extensive procedure was necessary and was done following the description of ref. [12] and [13]. In a first step, the absorption edge at 530 eV has been fitted by two Gaussian functions.…”
Section: Vdensity Of States At the Fermi Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing x decreases the c axis parameter of the unit cell but the number of holes increases in both CuO 2 plane and BiO layer [55]. The variation of the c axis parameter changes the coupling between the coupling of CuO 2 planes by changing their distance and thus their Josephson coupling.…”
Section: Resultsmentioning
confidence: 99%
“…Karppinen et al [55] showed that doping with yttrium at Ca site gives, for the concentrations used in our samples (remark: x corresponds to 1 -x in that work), an overdoped Bi-2212 phase which is nearly optimally doped for Y010 and Y025. Increasing x decreases the c axis parameter of the unit cell but the number of holes increases in both CuO 2 plane and BiO layer [55].…”
Section: Resultsmentioning
confidence: 99%